Drying characteristics and kinetics of bottle gourd using stand-alone indirect solar dryer - Al-Ghadani, Ohood; Al-Khayari, Mawada; Jayasuriya, Hemanatha; Pathare, Pankaj B.; Al-Belushi, Mohammed (Frontiers in Sustainable Food Systems, 2024)
Drying food is an effective method to preserve fruits and vegetables, increasing their shelf life and preventing germination. Bottle gourds, known for their high nutritional value, can rot quickly due to their high moisture content, causing biochemical and microbial changes. To improve shelf life, moisture can be removed to prevent microbial activity. Different drying methods are used to preserve gourd family vegetables for long periods and off-season. Indirect solar drying shields foods from UV rays, dust, insects, and other contamination by avoiding direct exposure. This study aimed to utilize an indirect solar dryer to research the potential for drying bottle gourds and conduct physicochemical analyses for the dried products to compare the drying techniques. In this experiment, different samples of bottle gourd slices were dried using an indirect solar dryer and compared with sun and shade drying. Under physicochemical properties, moisture content (MC), retention of color, thickness, and shrinkage of dried samples were analyzed and compared. The result showed that the time taken to reach 10% moisture was 13 h for samples dried with sun drying. While shade and indirect solar drying took 17 h. The Midilli-Kucuk model outperforms other approaches for drying bottle gourd, with the greatest R2 values (0.9967, 0.9950, 0.9936) and the lowest RMSE values (0.0182, 0.0220, 0.0277) for direct sun, shade, and indirect solar drying, respectively. The indirect sun dryer showed good color retention compared to the fresh bottle gourd samples with L* value of 44.08, b* value of 15.40 and a* value of 7.01. The volumetric shrinkage was 97.64% in the direct sun drying method after 15 h, which is higher compared to sun and shade dryers due to the effect of time and temperature. In addition, there was a significant difference (p-value <0.05) between the thickness of the three drying methods. The use of indirect solar drying methods can be highly recommended to get high-quality dried food with zero energy cost. For future studies it is recommended to enhance the function and design of the indirect solar dryer to speed up drying times and improve the quality of dried samples.